Law Enforcement in Indonesia: Exploration of the Concept of Justice in Islamic Dimension with Pancasila Ideology - Ucuk Agiyanto (Al-Hayat: Journal of Islamic Education, 2018)
Law enforcement in Indonesia is still not going well and is so alarming. The problem of law enforcement (law enforcement) always tends to be the imbalance of dynamic interactions between legal aspects in expectations or das swollen, with elements of the application of the law in reality das sein. The weakness of law enforcement in Indonesia today can be reflected in various resolutions of significant cases that have not been completed, one of which is the practice of corrupt corruption, but ironically the main actors are very few who are legally enforced. This fact is precisely the best compared to some cases involving small people. Judging from the study of philosophy, the reflection of legal philosophy is done to be able to know the irregularities that exist in the application of the law in looking at the value orientation of justice that concerns the view of human life. Because the code must always be returned to its original purpose to create justice, this study discusses Sidharta's conception of building and legal systems in examining the problem of law enforcement in Indonesia. The research method used in this paper is descriptive research, which aims to investigate law enforcement in Indonesia in terms of the study of the philosophy of law and law enforcement seen from the concept of Sidharta in creating justice law. Penegakan hukum di Indonesia masih belum berjalan dengan baik dan begitu memprihatinkan. Permasalahan penegakan hukum (law enforcement) selalu bertendensi pada ketimpangan interaksi dinamis antara aspek hukum dalam harapan atau das sollen, dengan aspek penerapan hukum dalam kenyataan das sein. Lemahnya penegakan hukum di Indonesia saat ini dapat tercermin dari berbagai penyelesaian kasus besar yang belum tuntas, salah satunya adalah praktek korupsi yang menggurita, namun ironisnya para pelaku utamanya sangat sedikit yang terambah hukum. Kenyataan tersebut justru berbanding terbaik dengan beberapa kasus yang melibatkan rakyat kecil. Dilihat dari kajian filsafat, refleksi filsafat hukum dilakukan untuk dapat mengetahui kejanggalan-kejanggalan yang ada dalam penerapan hukum dalam menilik orientasi nilai keadilan yang menyangkut pandangan hidup manusia. Sebab hukum harus selalu dikembalikan kepada tujuan awalnya untuk menciptakan keadilan. Penelitian ini membahas konsepsi Sidharta tentang bangunan dan sistem hukum dalam mengkaji masalah penegakan hukum di Indonesia. Metode penelitian yang digunakan dalam penulisan ini adalah penelitian deskriptif, yang bertujuan untuk mengkaji penegakan hukum di Indonesia ditinjau dari kajian filsafat hukum dan penegakan hukum dilihat dari konsep Sidharta dalam menciptakan hukum yang berkeadilan.